Root development in three tropical grass genotypes grown in contrasting soils and their potential for soil organic carbon accumulation - Mayorga, Mildred; Vázquez, Eduardo; Cardoso, Juan Andres (2025)
Grasses have significant potential for accumulating soil organic carbon, primarily due to their ability to translocate up to 60% of their gross primary production to belowground organs. Root depth is the most critical factor governing root carbon storage and stabilization in the soil. Urochloa humidicola is a tropical forage species well adapted to acidic, low-fertility soils and exhibits a high capacity for biological nitrification inhibition. Among its genotypes, CIAT679 and Bh08-1149 display contrasting root traits. Meanwhile, Mulato II is a Urochloa hybrid cultivar known for its high biomass production and forage quality. To compare carbon inputs and root development traits among the genotypes CIAT679, Bh08-1149, and Mulato II in two soil types—a high-fertility Vertisol and an acidic, low-fertility Oxisol—a rhizotron experiment was conducted under greenhouse conditions. After six months of growth, Mulato II exhibited the greatest root length, volume, surface area, and diameter, as well as the highest leaf area, photosynthetic rate, and photosystem II efficiency (ΦPSII). However, its root system grew in a more horizontal orientation. Among the U. humidicola genotypes, CIAT679 displayed superior root length, volume, and surface area. When comparing plant development across soil types, those grown in the Oxisol exhibited greater root length, surface area, volume, diameter, depth, and root orientation angle, along with higher photosynthetic rate and ΦPSII. This response is likely due to the Oxisol's higher sand content and lower clay fraction, which facilitate root exploration and growth. The enhanced root system in this soil type likely improves water and nutrient uptake, contributing to superior photosynthetic performance. Notably, the genotypes CIAT679 and Bh08-1149 grown in the Oxisol, developed the deepest roots and their greater root orientation angles indicate more vertical root growth.